Learners’ reflections and the Reflective Learning Experience in Linguistics - Nesrine, Ghaouar (Sciences humaines; Vol. 25 (2012): SCIENCES HUMAINES, 2014)
Effective learning is no more based on teacher centredness; however, it is the outcome of a learner centred approach which values learners’ contribution in their learning. For more committed learners who feel responsibility towards their learning, the reflective learning experience can be the clue. Learners will be involved in their learning inside and outside the classroom and the reflective journal will be of a great help to evidence their reflections on their learning. Furthermore, through their reflections on the reflective learning experience they have been involved in; first year learners of English have explained how it affected their learning of Linguistics. However, the implementation of a reflective learning experience is not easy and needs time.   التعلم الفعال هو نتاج نهج يرتكز على المتعلمين وﻴقدر مساﻫﻤﺘﻬ ﻢ في ﺘﻌﻠﻤﻬ ﻢ . لمتعلمين أكثر التزاما  يشعرون بالمسؤولية تجاه تعلمهم، يمكن  ﻠﻠتجربة  اﻠﺘﻔﻜ ﺮ ﻴﺔ ﺃ ﻦ   تكون ﺍﻟﺤ ﻞ .ﻤشارﻜﺔ  المتعلمين في التعلم داخل وخارج اﻠﻘﺴ ﻢ  و ﺍﻟمجلة  اﻠﺘﻔﻜ ﺮ ﻴﺔ  ستكون عونا كبيرا من أجل إثبات ﺘﻔﻜ ﺮ ﻫ ﻢ في ﺘﻌﻠﻤﻬ ﻢ . وعلاوة على ذلك، ﻔقد أوضح متعلمين السنة الأولى في اللغة الإنجليزية من خلال ﺘﺃﻤﻼﺘﻬ ﻢ ﺍﻠﻜﺘﺍﺒ ﻳ ﺔ كيف تأثر تعلمهم في اللغويات ﺒﺍﻠتجربة اﻠﺘﻔﻜ ﺮ ﻴﺔ